2016
DOI: 10.1007/s11664-016-4697-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen Partial Pressure on Opto-Electrical Properties, Crystallite Size and Dislocation Density of Sn Doped In $$_2$$ 2 O $$_3$$ 3 Nanostructures

Abstract: In this research, high-quality Sn doped indium oxide (ITO) thin films were grown on glass slide substrates using an electron beam evaporation method. Vacuum chamber partial pressure was changed and the electro-optical as well as the microstructure parameters were investigated. The microstructure of prepared films was evaluated by x-ray diffraction analysis in terms of crystallite size and dislocation density. It was found that the best results [high transparency (88%) over the visible wavelength region, low sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Therefore, two competing and contrary effects on the electrical resistivity are observed with the variation in P O 2 during the nanowire growth. First, the P O 2 dependence above 5 × 10 –3 Pa, i.e., the increase in electrical resistivity with P O 2 , is consistent with those of conventional n -type semiconducting metal oxides based on the reduced number of crystal imperfections including oxygen vacancies at a higher P O 2 . Second, the contrary effect below 5 × 10 –3 Pa must be originated from an event suppressing such crystal imperfections even under the reduced- P O 2 atmosphere. In the VLS nanowire growth process, two different crystal growth interfaces exist: LS and VS interfaces. , We have recently reported that the two crystal growth interfaces have different impurity incorporation probabilities during the nanowire growth .…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Therefore, two competing and contrary effects on the electrical resistivity are observed with the variation in P O 2 during the nanowire growth. First, the P O 2 dependence above 5 × 10 –3 Pa, i.e., the increase in electrical resistivity with P O 2 , is consistent with those of conventional n -type semiconducting metal oxides based on the reduced number of crystal imperfections including oxygen vacancies at a higher P O 2 . Second, the contrary effect below 5 × 10 –3 Pa must be originated from an event suppressing such crystal imperfections even under the reduced- P O 2 atmosphere. In the VLS nanowire growth process, two different crystal growth interfaces exist: LS and VS interfaces. , We have recently reported that the two crystal growth interfaces have different impurity incorporation probabilities during the nanowire growth .…”
supporting
confidence: 66%
“…The small P O 2 decrease leads to a significant increase in the nanowire resistivity over 2 orders of magnitude. In general, the resistivity of an n -type semiconducting metal oxide decreases under a reduced- P O 2 growth condition owing to the increased number of crystal imperfections including oxygen vacancies, which generate mobile electrons. It is worth noting that the observed P O 2 dependence of the VLS-grown SnO 2 nanowire resistivity is opposite to the general trend. As shown in Figure b, the conventional P O 2 dependence of the resistivity (higher P O 2 leads to a higher resistivity) was observed for SnO 2 thin films deposited under similar conditions to those of the nanowire growth.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…R is the spherical quantum point, E B presents the exciton binding energy, and a B shows the Bohr radius. This relation is reliable for small nanoparticles with a radius a B > R. Nevertheless, when the crystallite radius increases, the quantum dot size can be assumed to be half of the volume-weighted average crystallite size [48,49]. Also, there is a direct and linear relationship between the average constant strain and the energy gap [50]:…”
Section: Refractive Index and Extinction Coefficientmentioning
confidence: 99%
“…Therefore, atmospheric electrical stability of ZnO nanowire devices is an essential subject for a long-term big data correction achieved by utilizing chemical sensors, UV detectors, force/pressure sensors, and energy-harvesting generators . ZnO nanostructures are relatively reactive to both acids and bases, and during their preservation in air, oxygen and water have been considered to have the most effect on their physical properties due to their chemical reactivity. In addition, oxygen vacancies in the crystal, which react with oxygen and water in air, are widely recognized as electron donors in binary metal oxides such as ZnO, SnO 2 , and others; the formation/compensation of oxygen vacancies generates/eliminates mobile electrons. Other species in air are relatively inactive or low in content and have been considered to interact with metal oxide surfaces only under more reactive conditions such as high temperatures. , Since the electrical properties of nanostructures are inherently affected by many factors, including their interfaces and surfaces, achieving the atmospheric electrical stability of single-crystalline ZnO nanowires remains a challenging issue for their device application to interactive electronics in air.…”
Section: Introductionmentioning
confidence: 99%